Challenges and opportunities of artificial intelligence in African health space - Muslim A. Alaran; Salim Kamaludeen Lawal; Mustapha Husseini Jiya; Salihu Alhassan Egya; Mohamed Mustaf Ahmed; Abdullateef Abdulsalam; Usman Abubakar Haruna; Muhammad Kabir Musa; Don Eliseo Lucero-Prisno (Digital Health)
The application of artificial intelligence (AI) to healthcare in Africa has the potential to transform productivity, diagnosis, disease surveillance, and resource allocation by improving accuracy and efficiency. However, to fully realize its benefits, it is necessary to consider issues concerning data privacy, equity, infrastructure integration, and ethical policy development. The use of these tools may improve the detection of diseases, the distribution of resources, and the continuity of care. The use of AI allows for the development of policies that are tailored to address health disparities based on evidence. While AI may increase accessibility and affordability through telehealth, remote monitoring, and cost reductions, significant barriers remain. Ethical guidelines are needed to ensure AI decisions align with medical standards and patient autonomy. Strict privacy and security controls are crucial to protecting sensitive health data. This article evaluates the current and potential roles of AI in the African health sector. It identifies opportunities to address challenges through tailored interventions and an AI framework to simulate policy impacts.